Consensus building in Tunisia: A study from 2011 - 2013 - Ghanem, Amatelrauf Tawfik (AUC Knowledge Fountain, 2015)
In the wake of the Arab Spring that swept North Africa and the Middle East in late 2010, different processes of political change have been underway in the region with different results in the nature of each political system. Some transitioned to democracy while others to new forms of authoritarianism or underwent cosmetic reforms without any real effect on the nature of the system. The interest of this research is to examine transition to democracy. It focuses on Tunisia as a case where a democratic transition was initiated after toppling the Former President of Tunisia, Zine al-Abidine Ben Ali. Tunisia is widely regarded as the closest to democratic transition as the outcome of its respective process is somewhat clear: a negotiated constitution was approved and permanent institutions were elected. Thereby, this research explores how the literature on democratic transition has dealt with consensus, as well as the dynamics and mechanisms of the consensus-building process in transitional countries. In doing so, the study shall also highlight the nature and impact of negotiating successful or failed pacts between key actors in Tunisia and the concessions that have brought about successful or failed consensus. As a final conclusion, the study reflects the mechanisms deduced from the literature review on the Tunisian case and attempts to develop a theoretical framework for consensus building in transitions. The research findings reveals that the Tunisian transition process that took place from 2011 to 2013 serves as a significant example that Arab transition politics does not have to be a zero-sum game and that a consensus led democratic transition is achievable.